Right to the water, right to the city. Universalization of sanitation in precarious urban settlements of Medellin, Colombia - Furigo, Renata de Faria Rocha; Samora, Patricia Rodrigues; Gutiérrez Tamayo, Alberto Léon (Pontifícia Universidade Católica de São Paulo, 2020)
This article analyzes a sanitation universalization program in precarious urban settlements, implemented by the municipal government of Medellin, Colombia. Based on the theory of Political Ecology, it discusses aspects that enable or restrict the expansion of sanitation services to the poor population, and analyzes the experience of Bello Oriente, a settlement not served by the program, where the population, with the support of a local NGO, has managed to improve water supply conditions and mitigate geotechnical risks. The article shows that the solution developed by the community is much closer to a concept of socioenvironmental unit than the municipal urban policy, which proposes a development based on ecological urbanism, but is subject to the neoliberal model of commodification of the city.